Tanggung Jawab Perusahaan Farmasi dan BPOM Terhadap Produk Obat Sirup Anak - Agil Ahmad; Nova Krisyananti; Muh. Rafli Rumbia; Susanti Susanti; Moch Al Farih Rahim; Aslinda Aslinda; Muh. Alfayed Suherman; Putri Rifdah Amalia (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
Acute kidney failure caused by contaminated FG and DFG syrup drugs mixed with children's syrup drugs. Several other causes that allow kidney failure to occur have been ruled out because it is not proven that the Ministry of Health is working with BPOM to conduct research on recommended drugs for research.Health workers and the pharmaceutical industry are also encouraged by BPOM to continue to actively report drug side effects or unwanted events after drug unemployment to the national pharmaceutical center through the e-Meso mobile application.BPOM supervises business actors to ensure the safety of the raw materials used. This is due to the high level of contamination in syrup medicines which cannot be separated from the responsibility of the drug producer or industry.